Workforce exposure to rockfalls in underground mines - Owen, M.L. (SRDM 2009: Proceedings of the First International Seminar on Safe and Rapid Development Mining, 2009)
Risk assessment and workplace safety is a hot topic in the mining industry. Recent years of media interest have seen mine safety being dissected in the public domain. The application of risk analysis techniques to the management of personnel safety is being promoted by both industry and regulators but, particularly for geotechnical hazards, often there are inadequate databases for a meaningful quantitative calculation of risk. This paper presents an empirical model for quantifying the exposure of personnel to geotechnical hazards in underground mines. The exposure model parameters relate to temporal, spatial and vulnerability probabilities as developed by Owen (2004), using both empirical data and mechanistic principles. Ultimately, the model gives the relative level of exposure of mine personnel to rockfalls/rockbursts before converting the exposure rating to a probability of fatality, correlated with mining accident statistics. This allows the effectiveness of various risk reduction strategies to be more accurately assessed so efforts can be prioritised, bringing the mining industry more in line with risk assessment and reporting practices within the petrochemical sector.